One student at a time: How an innovative charter school succeeds with dropout recovery - Joe Lewis; Letitia Basford (National Youth Advocacy and Resilience Journal, 2020)
In this paper, the authors examine how a charter high school in a large upper-Midwest city is successfully serving students who have not succeeded in the traditional school system and are in danger of experiencing the school-to-prison pipeline. The school accomplishes this through its enactment of five key qualities: 1. A casual, family-like atmosphere; 2. Commitment to a small, close-knit community; 3. Creative responses to absenteeism; 4. Extreme patience and flexibility in the classroom; 5. Innovative, trade-focused programs. The authors also examine the central challenges the school faces as it works to serve this group effectively. The paper describes an overarching model for serving adolescents who have had adverse childhood experiences (ACES) – a philosophy and practice of pedagogical and institutional plasticity.